Probiotic Lactobacillus sp. as a strategy for modulation of non-comorbid obesity: A systematic meta-analysis and GRADE assessment of randomized controlled trials - Lele, Juan AJMN.; Sihaloho, Karlos B.; Vighneswara, Dewa; Rampengan , Derren DCH.; Rizqiansyah, Chrisandi Y.; Permatasari, Happy K.; Mayulu, Nelly; Tallei, Trina E.; Taslim, Nurpudji A.; Kim, Bonglee; Kezia, Immanuelle; Nurkolis, Fahrul; Syahputra, Rony A. (Narra J, 2025)
Given the high prevalence of obesity worldwide, effective therapeutic strategies are crucial to prevent and manage obesity-related health conditions. Existing studies indicate that Lactobacillus sp. showed beneficial effects on body weight and adiposity by modifying the gut microbiota; however, no meta-analysis has been conducted assessing the efficacy of Lactobacillus sp-based probiotics on anthropometric parameters, leptin and adiponectin levels, and gut microbiota composition. The aim of this study was to evaluate the efficacy and safety of probiotic supplementation with Lactobacillus sp. in obese individuals without comorbidities. A systematic search was conducted on November 28, 2024, using five databases: PubMed, Wiley, ScienceDirect, Epistemonikos, and Cochrane. Primary outcomes included changes in body mass index (BMI), body weight, waist and hip circumferences, visceral and subcutaneous fat areas, and total body fat content. Secondary outcomes included alterations in leptin and adiponectin levels, gut microbiota composition, and the incidence of adverse events. A total of 1,058 individuals were included across 12 clinical trials. Significant reductions were observed in BMI (mean difference (MD): -0.40 kg/m²; 95%CI: -0.48–(-0.32), p<0.00001), body weight (MD: -1.16 kg; 95%CI: -1.79–(-0.53), p=0.0003), waist circumference (MD: -1.41 cm; 95%CI: -1.75–(-1.08), p<0.00001), and hip circumference (MD: -0.85 cm; 95%CI: -1.09–(-0.61), p<0.00001) compared to controls. Additionally, compared to control group, significant reductions were observed in visceral and subcutaneous fat mass (MD: -7.35; 95%CI: -9.95–(-4.75); p<0.00001) and overall body fat (MD: -1.11; 95%CI: -1.31–(-0.91); p<0.00001). Leptin levels significantly decreased (MD: -2.11 μg/mL; 95%CI: -3.59–(-0.64), p=0.005) compared to before Lactobacillus sp. supplementation, while adiponectin levels increased (MD: 0.71 μg/mL; 95%CI: 0.22–1.20, p=0.004) following Lactobacillus sp. supplementation compared to placebo group. No significant adverse events were reported in either the intervention or control groups. In conclusion, Lactobacillus sp. probiotic supplementation may serve as an adjuvant therapy to enhance obesity management in non-comorbid obese individuals.